2021
DOI: 10.1002/ecs2.3742
|View full text |Cite
|
Sign up to set email alerts
|

Let's do the time warp again: non‐linear time series matching as a tool for sequentially structured data in ecology

Abstract: Ecological patterns are often fundamentally chronological. However, generalization of data is necessarily accompanied by a loss of detail or resolution. Temporal data in particular contain information not only in data values but in the temporal structure, which is lost when these values are aggregated to provide point estimates. Dynamic time warping (DTW) is a time series comparison method that is capable of efficiently comparing series despite temporal offsets that confound other methods. The DTW method is bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…While the Euclidean distance is faster, better known, and still widely used in some fields, an extensive body of research has shown DTW to be more accurate (Dau et al, 2019 ; Paparrizos et al, 2020 ; Zhu et al, 2012 ), and it is considered the de facto standard for accuracy in classification (note that it is still important to consider the properties of DTW in relation to the data, as it does not perform well in every case). Despite this, it is rarely used in ecology (Hegg & Kennedy, 2021 ). Note, however, that DTW is computationally expensive and therefore can be slow for large datasets (for discussion on ways to speed up DTW, see Appendix E ).…”
Section: Discussionmentioning
confidence: 99%
“…While the Euclidean distance is faster, better known, and still widely used in some fields, an extensive body of research has shown DTW to be more accurate (Dau et al, 2019 ; Paparrizos et al, 2020 ; Zhu et al, 2012 ), and it is considered the de facto standard for accuracy in classification (note that it is still important to consider the properties of DTW in relation to the data, as it does not perform well in every case). Despite this, it is rarely used in ecology (Hegg & Kennedy, 2021 ). Note, however, that DTW is computationally expensive and therefore can be slow for large datasets (for discussion on ways to speed up DTW, see Appendix E ).…”
Section: Discussionmentioning
confidence: 99%
“…While the Euclidean Distance is faster, better known, and still widely used in some fields, an extensive body of research has shown DTW to be more accurate (Zhu et al ., 2012; Dau et al ., 2019; Paparrizos et al ., 2020) and it is considered the de facto standard for accuracy in classification (note that it is still important to consider the properties of DTW in relation to the data, as it does not perform well in every case). Despite this, it is rarely used in ecology (Hegg and Kennedy, 2021). Note, however, that DTW is computationally expensive and therefore can be slow for large datasets (for discussion on ways to speed up DTW, see supplementary materials S11).…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic time warping (DTW) is a technique that seeks to minimize the distance between two time series by expanding or contracting the temporal axis to find the closest fit between the two time series (Hegg & Kennedy, 2021). More generally, it can be used to cluster multiple time series into similar groups.…”
Section: Benefits Over Alternative Methodsmentioning
confidence: 99%